Development of Bake Hardening Effect by Plastic Deformation and Annealing Conditions - Kvačkaj, T.; Mamuzić, I. (Metalurgija, 2006)
The paper deals with the classification of steel sheets for automotives industry on the basis of strength and structural characteristics. Experimental works were aimed to obtain the best possible strengthening parameters as well as work hardening and solid solution ferrite hardening, which are the result of thermal activation of interstitial carbon atoms during paint-baking of auto body. Hardening process coming from interstitial atoms is realized as two-step process. The first step is BH (bake hardening) effect achieved by interaction of interstitial atoms with dislocations. The Cottrels atmosphere is obtained. The second step of BH effect is to produced the hardening from precipitation of the carbon atoms in e-carbides, or formation of Fe32C4 carbides. WH (work hardening) effect is obtained as dislocation hardening from plastic deformations during sheet deep drawing. Experimental works were aimed at as to achieve such plastic material properties after cold rolling, annealing and skin-pass rolling, which would be able to classify the material ZStE220BH into the drawing categories at the level of DQ – DDQ. As resulting from the experimental results, the optimal treatment conditions for the maximal sum (WH+BH) = 86 MPa are as follows: total cold rolling deformation ecold = 65 %, annealing temperature Tanneal. = 700 °C.